Development Aid and Export Resilience in Developing Countries: A Reference to Aid for Trade - Sèna Kimm Gnangnon (Economies, 2022)
The COVID-19 pandemic, as with previous major crises, such as the 2008 financial crisis, has had a severe negative impact on international trade flows. The present paper aims to contribute to the debate concerning how to foster resilience against future crises, in terms of countries’ aggregate exports, by examining the effect of development aid (i.e., so-called official development assistance), particularly the impact of the Aid for Trade (AfT) component, upon export resilience. The resilience of exports refers to the ability of countries’ aggregate exports to resist shocks, regardless of whether they are environmental or external shocks. The core argument of the analysis is that development aid would affect export resilience through its impact upon productive capacities. The analysis covers 93 developing countries over the period 2002–2018. The findings indicate that the total development aid flows, including both AfT flows and NonAfT flows, exert a positive effect upon export resilience. Among AfT components, AfT for productive capacities appears to exert a greater positive effect upon export resilience than AfT for economic infrastructure and AfT for trade policy and regulation. In addition, development aid (regardless of which aid variable is considered) exerts the greatest positive effect upon export resilience in countries (such as the least developed countries—LDCs) that have the lowest productive capacities. These findings highlight the need for donor countries to supply higher development aid flows, in particular, AfT flows, to countries such as LDCs that have low productive capacities.